Is there life after death: from psychotherapeutic practice with adolescents after their true suicide attempt - Romanova E.V. (Консультативная психология и психотерапия, 2016)
Suicide attempts made by the patients suffering from depression should be considered as a special case in the general category of suicidal and self-injurious behavior. The paper is aimed at describing the examples of psychotherapeutic work with three 16-year-old teenagers who were diagnosed with severe depressive episode and had made a true suicide attempt. It explains the specificity of their mental status in dy- namic perspective. The set of the personal characteristics peculiar for such teenage pa- tients includes sensitivity, disposition to reflexivity, higher level of personal and social anxiety, self-esteem disturbance, cognitive distortions (negative selection, polarized thinking, personalization, catastrophizing), low frustration tolerance, perfectionism, low social competence, lack of problem-solving skills. On the basis of these and other cases of severe depressive episodes the author defines the goals for individual and family therapy, the possibilities and perspectives of psychotherapeutic treatment.